Mapping Literature on the Utilization of Project-Based Learning in Physics Education from 2018 to 2023: A Bibliometric Analysis - Ahmad Maqruf; Achmad Syamsuddin; Andi Suhandi (Jurnal Serambi Ilmu, 2024)
Project-based Learning (PjBL) was an active learning approach where students undertake in-depth investigations of topics or issues, aiming to produce tangible products or solutions. This literature mapping aims to offer an overview of the existing literature on project-based learning in Physics Education via bibliometric analysis. Utilizing the Scopus database, a data search was conducted, yielding 180 documents, with limitations applied based on specific criteria. Publications with the highest citation counts were identified from international journals indexed by Scopus, with a focus on quartile 3 journals. Using VOSviewer visualization, eight clusters were identified, highlighting the interconnectedness of project-based learning in physics education with courses, models, problems, and ability. Additionally, novel perspectives were explored to expand the application of PjBL in physics education. Future research opportunities lie in implementing PjBL in physics education to foster critical thinking, problem-solving abilities, creative thinking, student creativity, and metacognitive skills. Furthermore, future research endeavors could integrate PjBL with other methodologies, such as laboratory activities or STEM approaches. This analysis provides valuable insights into the current landscape of project-based learning in Physics Education and offers directions for future research endeavors.